English Learners’ Identity Formation as Low and High Investors in their Learning Process - Moná, Maritza Collazos; Gómez Rodríguez, Luis Fernando (Colombian Applied Linguistics Journal, 2019)
This article reports the fndings of a descriptive case study that analyzed how unfair social relationships established in an EFL (English as a Foreign Language) classroom inﬂuenced a group of adolescent English language learners’ academic investment and identity construction at a school in Bogotá, Colombia. Data associated with students’ social behaviors and identities were collected through feld notes, a questionnaire, and an interview. Norton’s theory of identity and investment served as the basis to analyze the data from a social perspective. Three main fndings emerged from the data: First, EFL learners identifed themselves as high investors and low investors in their learning, depending on their own opinions about the usefulness of English in their lives. Second, power relationships based on domination and oppression reduced productive investment in the classroom. Third, some high investors resisted unfair relationships of power by investing through collaborative learning. Consequently, participants created diverse English learners’ identities (dominant, submissive, resistant, and productive), which inﬂuenced their academic investment negatively or positively.